Global analysis of RNA-binding protein dynamics by comparative and enhanced RNA interactome capture - Perez-Perri, JI; Noerenberg, M; Kamel, W; Lenz, CE; Mohammed, S; Hentze, MW; Castello, A (Springer Nature, 2020)
Interactions between RNA-binding proteins (RBPs) and RNAs are critical to cell biology. However, methods to comprehensively and quantitatively assess these interactions within cells were lacking. RNA interactome capture (RIC) uses in vivo UV crosslinking, oligo(dT) capture, and proteomics to identify RNA-binding proteomes. Recent advances have empowered RIC to quantify RBP responses to biological cues such as metabolic imbalance or virus infection. Enhanced RIC exploits the stronger binding of locked nucleic acid (LNA)-containing oligo(dT) probes to poly(A) tails to maximize RNA capture selectivity and efficiency, profoundly improving signal-to-noise ratios. The subsequent analytical use of SILAC and TMT proteomic approaches, together with high-sensitivity sample preparation and tailored statistical data analysis, substantially improves RIC's quantitative accuracy and reproducibility. This optimized approach is an extension of the original RIC protocol. It takes 3 d plus 2 weeks for proteomics and data analysis and will enable the study of RBP dynamics under different physiological and pathological conditions.